Participation of Beneficiaries of RTE Act, 2009 in Schools - Chauhan, Poonam A.; Talegaonkar, Vandana (Voices of Teachers and Teacher Educators, 2019)
Education as a right came into effect with the enactment of RTE Act, 2009 which guarantees Free and Compulsory Education for the children age from 6 to 14 years. Section 12 (1) (C) of the RTE Act, 2009 deals with the provision of admission of twenty-five percent children from weak and disadvantaged group in all private unaided schools. The article presents the research study showing the nature of participation of beneficiaries admitted under RTE Act, 2009 in schools of Vadodara, Gujarat. The researchers have used survey method and have conducted non- participant observation in the classroom. The data collected was qualitative in nature. All the observations were noted minutely. The was analyzed using the process of coding. Coding was done and variables derived. Later, the variables were categorized using the rating scale- always, sometimes and never. The findings of the study reveals that majority of the beneficiaries are always paying attention in the class, focused on learning activity, bring needed material to the class, complete assigned work on time but very few beneficiaries express their views in the class because of language problem. It is however shown through the present study that the nature of participation of beneficiaries is the same as of students of schools where RTE Act is not implemented.